Characterization and comparison of environmental attitudes of Generation X, Y, and Z - Barbosa, Mariana Guerra (2021)
Due to impactful environmental issues such as global warming, air pollution, or natural resource depletion, there has been raising awareness and concern for the natural environment protection and preservation. This sense of responsibility has been particularly remarkable in younger generations who are now the face of the green movement. Therefore, it is essential to understand how these current generational cohorts, who are in charge of the environmental future, assess the environment. In order to do so, this master thesis characterizes and compares the environmental attitudes of Generation X, Y, and Z. The main objectives of the present study are to examine and describe the proposed generational cohorts' attitudes towards the protection of the environment and the factors affecting its quality, and to establish a comparison between the different reported degrees of favor or disfavor. To achieve the proposed goals, an online questionnaire was developed. The present study allowed the conclusion that in Portugal, Generation X's mean level of enjoyment of nature is the highest compared to other dimensions that compose the construct of environmental attitudes. Generation Y and Z reveal a ranking order similar to one another, showing high levels of enjoyment of nature and support for interventionist conservation policies. However, few relationships could be established between the different generations, and contrary to what was inferred, younger generational cohorts have not more pro-environmental attitudes that older ones.